2017
DOI: 10.1080/13588265.2017.1328723
|View full text |Cite
|
Sign up to set email alerts
|

On the assessment of the macro-element methodology for full vehicle crashworthiness analysis

Abstract: Very fast full vehicle simulations through the use of effective, but drastically simplified digital models is a topic of great interest to automotive manufacturers and research communities. A nonconventional modelling and simulation approach using the macro-element methodology, embedded in Visual Crash Studio (VCS), is assessed. Modelling practices for converting finite element models to macro-element models are developed and presented. A large number of automotive systems, ranging from components and sub-syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Artificial Neural Networks. Artificial neural network (ANN) is a nonlinear processing system formed by the interrelation of a large number of processing units [6]. Artificial neural network is a data model established by simulating the neurons of animals.…”
Section: Neural Network Control Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial Neural Networks. Artificial neural network (ANN) is a nonlinear processing system formed by the interrelation of a large number of processing units [6]. Artificial neural network is a data model established by simulating the neurons of animals.…”
Section: Neural Network Control Theorymentioning
confidence: 99%
“…e emergence of finite element method provides an effective tool for solving the problem [19]. e basic idea of the finite element method is to discretize a continuous solution region into a finite set of elements that are connected to each other in a certain way [6]. at is to say, a finite element set is used to replace the contiguous solution region with the same geometric shape or approximately the same geometry.…”
Section: Basic Idea Of Finite Elementmentioning
confidence: 99%
“…Several benchmark tests conducted by Takada and Abramowicz (2003) showed that MEM needs an incomparably shorter pre-processing time comparing to FEM (i.e., the calculation effort is much lower), and the resulting results present a high accuracy. The most recent assessment of MEM application in the crashworthiness analysis was conducted by Georgiou and Zeguer (2018). Their work investigates advantages and weak points of simplified crash phenomena modeling using MEM.…”
Section: Macro Element Methods and Visual Crash Studiomentioning
confidence: 99%
“…The modeling results using the VCS program of some typical problems have been validated in the past in many papers mentioned already in the chapters 3.1 and 3.2 (Takada and Abramowicz (2003); Georgiou and Zeguer (2018); Kim and Wierzbicki 2004). The validation of crashworthiness results for a thin-walled beam was presented, for example, in the previous work of authors, i.e., Pyrz and Krzywoblocki (2017).…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…They extended their study to the optimization of the front rail dimensions (2019). Georgiou and Zeguer (2018) carried out crash analysis of the whole vehicle and individual sub-assemblies separately using this method.…”
Section: Introductionmentioning
confidence: 99%